Stronger secondary pollution processes despite decrease in gaseous precursors: A comparative analysis of summer 2020 and 2019 in Beijing. (15th June 2021) - Li, Hui; Ma, Yongliang; Duan, Fengkui; Zhu, Lidan; Ma, Tao; Yang, Shuo; Xu, Yunzhi; Li, Fan; Huang, Tao; Kimoto, Takashi; Zhang, Qinqin; Tong, Dan; et al.
Abstract: To control the spread of COVID-19, China implemented a series of lockdowns, limiting various offline interactions. This provided an opportunity to study the response of air quality to emissions control. By comparing the characteristics of pollution in the summers of 2019 and 2020, we found a significant decrease in gaseous pollutants in 2020. However, particle pollution in the summer of 2020 was more severe; PM2.5 levels increased from 35.8 to 44.7 μg m −3, and PM10 increased from 51.4 to 69.0 μg m −3 from 2019 to 2020. The higher PM10 was caused by two sandstorm events on May 11 and June 3, 2020, while the higher PM2.5 was the result of enhanced secondary formation processes indicated by the higher sulfate oxidation rate (SOR) and nitrate oxidation rate (NOR) in 2020. Higher SOR and NOR were attributed mainly to higher relative humidity and stronger oxidizing capacity. Analysis of PMx distribution showed that severe haze occurred when particles within Bin2 (size ranging 1–2.5 μm) dominated. SO4 2− (1/2.5) and SO4 2− (2.5/10) remained stable under different periods at 0.5 and 0.8, respectively, indicating that SO4 2− existed mainly in smaller particles. Decreases in NO3 − (1/2.5) and increases in NO3 − (2.5/10) from clean to polluted conditions, similar to the variations in PMx distribution, suggest that NO3 − played a role in the worsening of pollution. O3 concentrations were higher in 2020 (108.6 μg m −3 ) than in 2019 (96.8 μg m −3 ). Marked decreases in fresh NO alleviated the titration of O3 . Furthermore, the oxidation reaction of NO2 that produces NO3 − was dominant over the photochemical reaction of NO2 that produces O3, making NO2 less important for O3 pollution. In comparison, a lower VOC/NOx ratio (less than 10) meant that Beijing is a VOC-limited area; this indicates that in order to alleviate O3 pollution in Beijing, emissions of VOCs should be controlled. Graphical abstract: Image 1 Highlights: Precursors were significantly reduced by COVID-19 lockdown in summer 2020. Stronger secondary processes caused higher particle pollution in summer 2020. Beijing is VOC-limited in O3 pollution. Abstract : Haze pollution in summer 2020 was more severe because of the stronger secondary processes despite the rapid decrease of precursors caused by the COVID-19 lockdown.